2017
DOI: 10.1007/s11606-017-4051-9
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid’s Impact on Chronic Disease Biomarkers: A Cohort Study of Community Health Center Patients

Abstract: NCT02355132 [ https://clinicaltrials.gov/ct2/show/NCT02355132 ].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…However, our analyses adjusted for multiple factors that can influence achievement of control. Second, the funding agency set HbA1c < 9% for diabetes control, similar to other studies in Medicaid enrollees [20]. Yet, a reduction of HbA1c to < 9% would not protect against diabetes-related complications [21].…”
Section: Variablementioning
confidence: 99%
“…However, our analyses adjusted for multiple factors that can influence achievement of control. Second, the funding agency set HbA1c < 9% for diabetes control, similar to other studies in Medicaid enrollees [20]. Yet, a reduction of HbA1c to < 9% would not protect against diabetes-related complications [21].…”
Section: Variablementioning
confidence: 99%
“…43 Additionally, patients with diabetes and hypertension were significantly more likely to gain control of uncontrolled hemoglobin A 1c levels and blood pressure readings when comparing insured with matched uninsured CHC patients. 44 The percentage of insured patients seen in a clinic also affects the clinic's ability to provide needed health care services to all patients. 45,46 For example, CHCs with a higher percentage of insured patients provided all patients with superior levels of recommended care than clinics caring for a lower percentage of insured patients.…”
Section: Implications For Patients and Chcsmentioning
confidence: 99%
“…After the ACA Medicaid expansion, CHCs in expansion states improved in 4 out of 8 measures of preventive and chronic disease management relative to CHCs in nonexpansion states (Cole et al, 2017). One study using laboratory test results for patients in the Oregon Health Insurance Experiment found that individuals gaining coverage experienced improved control of diabetes and high blood pressure, but not high cholesterol, in the 2 years after insurance expansion compared with a matched group of uninsured patients at the CHCs (Hatch et al, 2017).…”
Section: Resultsmentioning
confidence: 99%